Neurocognitive Recovery After Hospital-Treated Deliberate Self-Poisoning With Central Nervous System Depressant Drugs: A Longitudinal Cohort Study. Issue 6 (December 2015) - Oxley, Stewart O. C.; Dassanayake, Tharaka L.; Carter, Gregory L.; Whyte, Ian; Jones, Alison L.; Cooper, Gavin; Michie, Patricia T.
Abstract : Abstract: Hospital-treated deliberate self-poisoning (DSP) by central nervous system depressant drugs (CNS-D) has been associated with impairments in cognitive and psychomotor functions at the time of discharge. We aimed to replicate this finding and to compare recovery in the first month after discharge for CNS-D and CNS nondepressant drug ingestions. We also examined a series of multivariate explanatory models of recovery of neurocognitive outcomes over time. The CNS-D group was impaired at discharge compared with the CNS-nondepressant group in cognitive flexibility, cognitive efficiency, and working memory. There were no significant differences at discharge in visual attention, processing speed, visuomotor speed, or inhibition speed. Both groups improved in the latter measures over 1 month of follow-up. However, the CNS-D group's recovery was significantly slower for key neurocognitive domains underlying driving in complex traffic situations, namely, cognitive flexibility, cognitive efficiency, and working memory. Patients discharged after DSP with CNS-D drugs have impairments of some critical cognitive functions that may require up to 1 month to recover. Although more pre- than post-DSP variables were retained as explanatory models of neurocognitive performance overall, recovery over time could not be explained by any one of the measured covariates. Tests of cognitive flexibility could be used in clinical settings as a proxy measure for recovery of driving ability. Regulatory authorities should also consider the implications of these results for the period of nondriving advised after ingestion of CNS-D in overdose. Future research, with adequate sample size, should examine contributions of other variables to the pattern of recovery over time. Abstract : Supplemental digital content is available in the text.